Molten salt synthesis and spectral properties of Nd3+ doped CdNb2O6 columbite phosphors - EKMEKÇİ, METE KAAN; ERDEM, MURAT (ELSEVIER SCIENCE SA, 2014)
Pure and Nd-doped CdNb2O6 particles have been prepared by a molten salt method using cadmium nitrate, niobium oxide and Li2SO4-Na2SO4 salt mixture as a flux at a relatively low temperature as compared to solid-state reaction method. X-ray diffraction patterns of the pure CdNb2O6 samples exhibited a single orthorhombic phase. Photoluminescence (PL) properties of all the undoped and Nd-doped samples in visible and near-infrared spectral region were studied in detail. While a strong blue emission band centered at 460 nm at room temperature was observed for the pure CdNb2O6, additional characteristic luminescence of Nd3+ at 1.06 mu m was observed for Nd-doped CdNb2O6. Concentration quenching phenomenon was detected depending on the Nd-doping concentrations at both room and relatively low temperatures. This characteristic of the doped samples may be ascribed to the energy transfer between Nd3+ and niobate groups (NbO6). (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Columbite niobates; Phosphors; Molten salt route; Concentration quenching; CRYSTAL-STRUCTURE; GROWTH